Evaluation of energy, carbon dioxide, and air emission implications of medium- and heavy-duty truck electrification in the United States using EPA’s regional TIMES energy systems model - Andrew Zalesak; Noah Kittner; Daniel H Loughlin; Pervin Ozge Kaplan (Environmental Research: Energy)
Electrifying on-road trucking is a strategy for decarbonizing the transportation sector. While battery-electric trucks have zero tailpipe emissions, the associated increase in electric sector grid emissions would offset a portion of on-road emission reductions. We utilize a techno-economic energy systems optimization model to assess the system-wide carbon dioxide (CO _2 ) and air pollutant emission implications of medium- and heavy-duty truck electrification in the United States of America. Results suggest that by transitioning to 100% battery-electric medium- and heavy-duty vehicles (MDVs and HDVs, together MHDVs), sales by 2050 would result in net CO _2 emission benefits should the electric sector decarbonize simultaneously. Combining a tax of $100 per ton of CO _2 , increasing at 5% per year, with electrification targets would yield a net 52% reduction in energy system CO _2 emissions in 2050. Across regions, the transportation sector nitrogen oxide (NO _X ) emissions—an ozone precursor—further decrease by 9%–26% compared to the ‘business-as-usual’ (BAU) level in 2050. The level of emission reductions and the extent of transportation decarbonization are driven by vehicle cost and performance projections along with underlying assumptions on the time of charging.